Pengaruh Kompetensi Technological Pedagogical Content Knowledge (TPACK) Terhadap Keterampilan Guru SMK Dalam Merancang Perangkat Pembelajaran Berbasis Digital - Komang Hari Santhi Dewi; I Putu Gede Abdi Sudiatmika; , Rifky Lana Rahardian; I Made Pradipta (Departement of Mathematics Education, 2024)
Integrating technology in learning with pedagogical and content mastery will achieve quality learning, known as a frameworkTechnological Pedagogical Content Knowledge (TPACK). Therefore, this research aims to determine the influence of competence TPACK on the skills of vocational school teachers in designing digital-based learning tools. This type of research is quantitative descriptive with a correlational model. Sampling used purposive random sampling, namely vocational school teachers in South Kuta District with a total of 49 people. Data collection techniques use questionnaire instruments and assessment rubrics for digital learning tools. Testing the quality of the instrument was carried out by analyzing the validity, and reliability of the instrument, and media expert testing. The analysis technique uses simple linear regression. The research results show that there is a positive and significant relationship between competencies TPACK and vocational school teachers' skills in designing digital-based learning tools with a correlation coefficient of 0.323 and a significance value of 0.00. Competency contribution TPACK of vocational school teachers' skills in designing digital-based learning devices is 89.50%.